Extinction, genealogy, and institutionalization: Challenging normative values in popular endangered language discourse. Issue 4 (1st October 2016) - Parks, Elizabeth S.; Nishime, Leilani
ABSTRACT: News accounts of the recent discovery of Hawai'i Sign Language tell of the identification of a new language—one nearing extinction—and, ultimately, the happy ending of language preservation. By applying postcolonial and disability studies scholarship to the news coverage, we reframe marginalized languages through an alternative logic. We examine the narratives of extinction, genealogy, and institutionalization that underlie both colonial and ableist discourses in the articles. We argue that popular conceptions of endangered language and language purity obscure how normative values are applied to language communities and institutionalization, often at the expense of those very communities.